A novel recombinant human collagen hydrogel as minced split-thickness skin graft overlay to promote full-thickness skin defect reconstruction. Issue 1 (February 2023) - Liu, Tong; Qiu, Chao; Lu, Hao; Li, Haihang; Zhu, Shihui; Ma, Lijie
Abstract: To overcome limited donor-site availability in patients with extensive burns, split-thickness skin grafts (STSGs) are sometimes minced into micrografts (MGs) to improve the expansion ratio of the grafts, but this may reduce wound healing. We aimed to produce a novel hydrogel as an overlay of minced STSGs to improve wound healing. The new hydrogel was produced using recombinant human collagen type III powder as a raw material. Morphological and physical characteristics (degradation and swelling rate), cytotoxicity, and cell viability of the hydrogel were evaluated in vitro. A full-thickness in vivo skin defect model was constructed with male Sprague-Dawley rats. The animals were randomly assigned to experimental and control groups in which the new hydrogel and Vaseline gauze, respectively, were overlaid on minced STSGs to repair and regenerate skin wound. The healing rates and recovery status were compared between the two groups. The hydrogels exhibited good water retention properties and a suitable degradation rate, which can promote the proliferation and migration of wound healing-related cells in vitro. Further, using the hydrogel as an overlay accelerated wound closure and angiogenesis, increased dermal tissue and basement membrane formation, enhanced collagen synthesis and wound healing-related growth factor expression, while reducing scar formation compared to the Vaseline gauze group. In conclusion, the novel, low-cost recombinant human collagen hydrogel can accelerate wound closure and improve wound healing when used as an overlay of minced STSGs. The new hydrogel could become a new treatment option for traumatic skin wounds caused by burns or injuries. Highlights: The preparation process of the novel recombinant human collagen hydrogel (RHCH) is simple and low-cost. RHCH promotes proliferation and migration of cells essential for wound healing in vitro experiments. RHCH can increase the wound healing rate while improving the quality of wound healing in vivo experiments.